Microeconomic Evidence of Creative Destruction in Industrial and Developing Countries - Eric J. Bartelsman; John Haltiwanger; Stefano Scarpetta (Tinbergen Institute, 2004)
In this paper we provide an analysis of the process of creative destruction across 24 countries and 2-digit industries over the past decade. We rely on a newly assembled dataset that draws from different micro data sources (business registers, census, or representative enterprise surveys). The novelty of our approach is in the harmonisation of firm level data across countries, which enables international comparisons and the identification of country-specific factors as opposed to sectoral and time effects. All countries display a massive reallocation of resources, with the entry and exit of many firms in all markets, the failure of many newcomers and the expansion of successful ones. This process of creative destruction affects productivity directly, by reallocating resources towards more productive uses, but also indirectly through the effects of increased market contestability. There are also large differences across groups of countries. While entry and exit rates are fairly similar across industrial countries, post entry performance differs markedly between Europe and the U.S., a potential indication of the importance of barriers to firm growth as opposed to barriers to entry. Transition economies show an even more impressive process of creative destruction and, amongst them, those that have progressed the most towards a market economy show better outcomes from this process. Finally, Mexico shows large firm dynamics with many new firms entering the battle but also many failing rapidly, while Argentina resembles more of Continental Europe with smaller flows and less impressive post-entry growth of successful firms.
Keywords: L11; G33; D92; 330; entry; exit; survival; firm size; productivity; micro data; Strukturwandel; Markteintritt; Unternehmenserfolg; Unternehmensstatistik; Welt; Marktaustritt